Kristen dan Teknologi: Etika, Literasi dan Ciptaan : Christianity and Technology: Ethics, Literacy and Creation - Andreas Maurenis (Jurnal Teologi Amreta (ISSN: 2599-3100))
With ethical awareness, literacy abilities, and awareness as God's intelligent creatures, Christians in various dynamics of life must continue to show a human ethics and spirituality, especially in the context of Christian ethics and spirituality. The Christians are able to use the results of the development of science and technology in digital systems. Although, learning, supervision and self-control as God's people are things that are constantly attached to it. With the advance and increasing number of scientific and technological discoveries in various forms, Christians are challenged to publicize themselves and their discipleship calls in the context of digital technology with various media. Christianity and technology become important topics of study that can be included in the umbrella of the great scientific knowledge of theology and science which have been under-attention in certain denominations. Christianity and technology as an academic discourse in lecture classes will be very applicable in the broad life of students and the Christian community in the future, especially by including the ethics, literacy, and creation as sub-topics in it. This discussion has become very important in the age of technology so that understanding and behavior of how Christians should place themselves in the midst of new challenges in the real new age is now being managed with adulthood. ==== Dengan kesadaran beretika, kemampuan literasi, dan kesadaran sebagai makhluk ciptaan Tuhan yang cerdas maka umat Kristiani dalam berbagai dinamika hidup mesti tetap memperlihatkan sebuah etika dan spiritualitas manusia, terutama dalam konteks etika dan spiritualitas Kristiani. Umat Kristen terbilang mampu menggunakan hasil perkembangan sains dan teknologi dalam sistem digital. Meskipun pembelajaran, pengawasan dan penguasaan diri sebagai umat Tuhan merupakan hal-hal yang terus-menerus melekat di dalamnya. Majunya dan semakin banyaknya temuan sains dan teknologi dalam berbagai bentuk, membuat umat Kristiani ditantang untuk mempublikasikan diri dan panggilan pemuridannya dalam konteks berteknologi digital dengan berbagai media. Kristen dan teknologi penting menjadi satu pokok bahasan kajian yang bisa dimasukkan ke dalam payung keilmuan besar teologi dan sains yang selama kurang diperhatikan dalam denominasi tertentu. Kristen dan teknologi sebagai satu diskursus akademik di dalam kelas-kelas perkuliahan akan menjadi sangat aplikatif dalam kehidupan luas mahasiswa dan masyarakat Kristiani di kemudian hari apalagi dengan menyertakan sisi etika, literasi, dan ciptaan sebagai sub-sub bahasan di dalamnya. Pembahasan ini menjadi amat penting di zaman teknologi agar pemahaman dan perilaku bagaimana seharusnya umat Kristiani menempatkan dirinya di tengah-tengah tantangan baru di zaman baru yang nyata sekarang ini menjadi terkelola dengan dewasa.